Distribution Characteristics of Heavy Metals in Sediments and Their Relationship with Benthic Fauna in the Clam Mudflat Aquaculture Area of Rudong, Jiangsu Province, China - Haopeng HU; Lei LI; Wei TIAN; Shuai HAN; Fengbiao WANG; Mei JIANG (Progress in Fishery Sciences)
Mudflats, located at the land-sea interface, are extremely rich in ecological resources. They are an important spatial carrier for human survival and development and are notably influenced by human activities. The rapid social and economic development of coastal areas has led to increased pollutants being discharged into the coastal waters with water flow, which seriously affects the coastal aquatic ecological environment. Sediment is the sink for most pollutants, including nutrients, heavy metals, and organic compounds. Pollutants can be enriched in sediments through physical changes such as adsorption, accumulation, and precipitation. When the water environment conditions change, the pollutants in sediments are released into the overlying water, affecting the aquatic ecosystem's health. Biological activities destroy the physical structure of the sediment-water micro-interface, change the oxygen content at the interface, induce the movement of sediment particles, bring the interstitial water out of the sediment interface, and promote the release of heavy metals in the sediments. Heavy metal pollutants are inherently toxic, persistent, and difficult to degrade, leading to many serious environmental problems and posing significant health risks. Therefore, evaluating the risk of heavy metal pollution in surface sediments as an important reservoir of heavy metal pollutants is necessary. This provides a scientific basis for the ecological management and restoration of mudflats. Presently, most studies on heavy metal pollution in the sediments of Rudong mudflats focus on the source of heavy metal elements and the evaluation of biotoxicity. Studies on the correlation analysis of the distribution characteristics of heavy metals in the Rudong mudflats and the distribution characteristics of benthic animals in the Rudong mudflats are scarce.In this study, the distribution characteristics of seven heavy metal elements in the sediments of the Rudong Meretrix meretrix aquaculture area were analyzed, and the potential ecological risk index method was used to evaluate the environmental risk of heavy metals in the sediments of the aquaculture area. Meanwhile, the correlation analysis between the distribution of zoobenthos and heavy metal pollution was performed to provide a reference for the ecological environment of the M. meretrix mudflats in Rudong and the sustainable development of the clam mudflat resources. Four field surveys were conducted in September and December 2022 and April and July 2023 in the M. meretrix mudflat aquaculture area in Rudong, Jiangsu Province. The contents of Zn, Cr, Cu, Pb, As, Hg, and Cd in the surface sediments were determined, and the characteristics of benthic communities were analyzed. The pollution risk assessment of heavy metals in surface sediments was conducted using the potential ecological index method, and the response relationship between heavy metal pollution in sediments and the distribution of benthic animals was analyzed. The results showed that the average contents of heavy metals in the surface sediments were in the order of Cr > Zn > Pb > Cu > As > Cd > Hg, and the contents of Zn, Cu, Pb, As, Hg, and Cd were in accordance with the quality standard of one type of marine sediments. The highest value and summer average value of Cr exceeded the first-class standard of marine sediment quality and met the second-class standard of marine sediment quality. The annual comprehensive potential ecological risk index ranged from 90.49 to 145.78, averaging 110.68. Regarding the classification of potential ecological risk, the overall risk level of the M. meretrix aquaculture area was at the medium risk level, and the order of individual potential ecological risk of each heavy metal element was Cd > Hg > As > Pb > Cu > Cr > Zn. The ecological risks of each sampling station were mainly from Cd, Hg, and As. Sampling was performed four times. The heavy metal Cd was the primary contributor to potential ecological risk and sediment pollution in the Rudong mudflats. Cd, Hg, and Cu are important components of industrial sewage discharge, and the land-based inputs and other pathways are their main sources. As is uncommon in natural environments, it is a primary component of chemical fertilizers and pesticides. The use of pesticides in the mudflat shellfish aquaculture area may be the main source of the As pollution. Most of the Pb in the sediments originates from atmospheric deposition and is linked to the pollution emission of fishing ports and ships in the region. Zn is related to the zinc plating and machinery manufacturing industries, while Cr is applied in large quantities in the chemical and chromium-plating industries. A total of 68 species of macrobenthos were collected in the four samplings. The richness index d ranged from 0.74 to 5.01 (SD=±1.19), the evenness index J' ranged from 0.25 to 0.92 (SD=±0.15), and the diversity index H' ranged from 0.99 to 3.79 (SD=±0.65) at each sampling station. The mean values of the diversity index H' for spring, summer, autumn, and winter were between 2 and 3, respectively. Compared with the biodiversity index evaluation criteria, the biodiversity of the four seasons belonged to a relatively rich level, and the habitat level was at a 'general' level. The density of polychaetes in the benthic animals had a significant negative correlation with Cu, Pb, Cr, and Cd heavy metal element index and RI. A significant negative correlation existed between the benthic animal richness index d and the heavy metal element indexes of Pb, Cr, and As.